PERANAN SISTIM INFORMASI MANAJEMEN BAGI ORGANISASI PUBLIK - Warno, Warno (STIE YPPI Rembang, 2009)
AbstractThe development of public organizations in the context of the state administration has been so rapid in Management Information Systems, both at the level of development of both theoretical and empirical context. Theoretically, organizational theory has evolved not only limited to formal organizational terms, often associated with bureaucracy. Starting from the distinction Search Public and Private Organizations, Public and Private Organizational Characteristics and tried several approaches used to identify public organizations (Caiden, 1987). For public management information systems. In the framework of management information systems actually are two concepts that relate directly to decision-making, namely SDS, structured decision system with the DSS, decision support system (Gorry and Morton in Golembiewski).Key words: management information systems, decision structurted system, DSS